PENGEMBANGAN MEDIA PEMBELAJARAN BLOG PADA MATERI SIFAT CAHAYA KELAS V SDN KEDUNGOTOK I JOMBANG - Slamet . (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2017)
ABSTRACT The fact that computers and laptops have become commonplace for the needs of learners today. it also occurs at the primary school level learners. Based on the limited observations the researchers showed that the development of technology, information, and communication is now also extended to students of primary school, many children holding a cell phone. On the other hand the study of students we know are still not satisfactory so that the general quality of education in Indonesia is still cause for concern. Based on the survey that the order of education in Indonesia occupies the lower group. One of the reasons happens because of the specific problems in education, ranging from lack of physical infrastructure in the learning process to the low equity of learning opportunity. The impact of the problems poor learning outcomes of students and quality of education is not satisfactory nationally is very pronounced when competing with neighboring countries and other countries that are already developed. Likewise, the impact of technological development, information and communication to the world of learning when teachers do not adjust the media will miss in their teaching. Media blog as a medium of learning as an option that can be used to study the nature of light on the subjects of natural science. KEYWORDS: instructional media, blog, nature of light ABSTRAK Kenyataan bahwa komputer dan laptop sudah menjadi hal biasa bagi kebutuhan peserta didik sekarang ini. hal tersebut juga terjadi pada peserta didik tingkat sekolah dasar. Berdasarkan pengamatan terbatas peneliti menunjukkan bahwa perkembangan teknologi, informasi, dan komunikasi sekarang juga merambah ke peserta didik sekolah dasar, banyak anak bila di rumah memegang telepon genggam. Pada sisi lain hasil belajar peserta didik kita ketahui masih belum memuaskan sehingga secara umum mutu pendidikan Indonesia juga masih memprihatinkan. Berdasarkan survey bahwa urutan pendidikan di Indonesia menempati kelompok bawah.Salah satu penyebab hal tersebut terjadi karena banyaknya permasalahan spesifik dalam pendidikan, mulai dari rendahnya sarana fisik dalam proses pembelajaran sampai rendahnya pemerataan kesempatan belajar. Dampak dari permasalahan rendahnya hasil belajar peserta didik dan mutu pendidikan yang belum memuaskan secara nasional tersebut sangat terasa ketika bersaing dengan Negara tetangga maupun negara lain yang sudah maju. Demikian juga dampak dari perkembangan teknologi, informasi, dan komunikasi terhadap dunia pembelajaran bila guru tidak menyesuaikan media akan ketinggalan dalam cara mengajarnya. Media blog sebagai media pembelajaran sebagai salah satu pilihan yang dapat digunakan untuk pembelajaran sifat cahaya pada mata pelajaran ilmu pengetahuan alam. KATAKUNCI: media pembelajaran, blog, sifat cahaya